Utilization of Pneumatic E-Module in Basic Vocational Process Learning for Students of SMK Negeri 3 Yogyakarta - Mairina, Mairina; Jatmiko, Heru (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to analyze the utilization of a pneumatic e-module as a learning medium in the Basic Vocational Mechanical Process subject for students at State Vocational School 3 Yogyakarta. Methodology This research employed a quantitative descriptive approach. The e-module was developed using the Daryanto module development model and the Pressman waterfall model (analysis, design, coding, testing) with Lectora Inspire software. Data were collected through observation, interviews, black box testing, and questionnaires, then analyzed using descriptive statistics. Main Findings: The e-module was validated as "good" by material experts (average score 114) and media experts (112.5). Teacher trials yielded an average score of 154.33 ("good"), and student trials resulted in 141.73 ("good"). The findings indicate the e-module is feasible and effective for use, with students finding the interactive multimedia content helpful for understanding pneumatic concepts. Novelty/Originality of this study: This research offers a novel, specifically designed pneumatic e-module for vocational education that integrates text, animations, simulations, and videos. It advances existing knowledge by providing an interactive, standalone digital medium for the Basic Vocational Mechanical Process subject, addressing a gap in media for pneumatics learning and offering a flexible tool for both classroom and independent study